Safety and Security Analysis of VVER-1200 Reactor Pressure Vessel Under Pressurized Thermal Shock - Mohammed Sarim Salman Karim; Dr. Debashis Datta; Altab Hossain (International Journal of Nuclear Security, 2024)
The reactor pressure vessel (RPV) is an important component of a nuclear power plant and of great concern to safety and security globally. Thus, the thermal system of an RPV should be ensured properly through an evaluation system that closely monitors and considers its integrity. This article describes the thermomechanical analyses for a pressurized thermal shock (PTS) scenario of a VVER-1200 RPV owing to a loss of coolant accident (LOCA) and activation of the emergency core cooling system (ECCS). The LOCA transient and activation of ECCS are modeled using ANSYS simulation software. From the analyses of the emergency core cooling injection owing to a LOCA in a PTS scenario, the transient flow distribution and the temperature profile evolution in the RPV wall are evaluated. Subsequently, the stress history in different situations for this transient was computed using thermal loads to show the safety of the VVER-1200.
Keywords: pressurized thermal shock; VVER-1200; reactor pressure vessel